Finite element analysis of concrete filled lean duplex stainless steel columns. (October 2019) - Lam, Dennis; Yang, Jie; Dai, Xianghe
Abstract: In recent years, a new low nickel content stainless steel (EN 1.4162) commonly referred as 'lean duplex stainless steel' has been developed, which has over two times the tensile strength of the more familiar austenitic stainless steel but at approximately half the cost. This paper presents the finite element analysis of concrete filled lean duplex stainless steel columns subjected to concentric axial compression. To predict the performance of this form of concrete filled composite columns, a finite element model was developed and finite element analyses were conducted. The finite element model was validated through comparisons of the results obtained from the experimental study. A parametric study was conducted to examine the effect of various parameters such as section size, wall thickness, infill concrete strength, etc. on the overall behaviour and compressive resistance of this form of composite columns. Through both experimental and numerical studies, the merits of using lean duplex stainless steel hollow sections in concrete filled composite columns were highlighted. In addition, a new formula based on the Eurocode 4 was proposed to predict the cross-section capacity of the concrete filled lean duplex stainless steel composite columns subjected to axial compression.